Medical Student Role in the Cardiothoracic Operating Room: A Needs Assessment to Optimize Engagement - Kayla N. Laraia, MD; Nathaniel Deboever, MD; Dylan Nieman, MD, PhD; Mara B. Antonoff, MD (Annals of Thoracic Surgery Short Reports)
Background: Focused preparation for the cardiothoracic operating room (CTOR) may optimize intraoperative engagement and medical student interest, but such resources are lacking. We sought to characterize student educational needs in the CTOR to guide resource development. Methods: A web-based survey targeting cardiothoracic surgeons, trainees, and operating room staff was distributed to identify areas for student improvement in the CTOR. Concepts investigated explored common student mistakes and expectations for knowledge and participation in the CTOR. Descriptive analyses were performed on multiple-choice polls and open-ended responses. Results: Polls received a mean of 317 responses (range, 222-504) and 20 open-ended comments. The most frequently cited student mistake was failure to understand their role in the CTOR (164 [32.5%]), followed by inappropriate chatting (141 [28.0%]) and breaking sterility (132 [26.2%]). Poll respondents valued students’ understanding of how to be helpful in the CTOR (101 [45.5%]) in addition to knowing what can or cannot be touched (47 [21.2%]) and basics of cardiopulmonary bypass (43 [19.4%]). Respondents indicated that students should assume active roles (84 [36.7%]), ask questions (66 [29%]), and help with minor tasks (41 [17.9%]). Respondents reported that students benefited most when they understood patient-specific clinicopathologic factors and basic operative steps. Conclusions: We identified several areas for student improvement in the CTOR. Development of educational resources addressing these issues may enhance interest and augment recruitment of students to cardiothoracic surgery.